2010
DOI: 10.2967/jnumed.108.061689
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assay of Folate Receptors in Nonfunctional Pituitary Adenomas with 99mTc-Folate SPECT/CT

Abstract: The objective of this study was to evaluate the in vivo assay of folate receptors in nonfunctional pituitary adenomas using preoperative 99m Tc-folate SPECT/CT and Western blot analysis (WBA) of surgical specimens as the standard. Methods: Fifty-six patients (29 men, 27 women; age range, 29-82 y) with clinically nonfunctional pituitary adenomas on MRI underwent preoperative imaging using 666 MBq (18 mCi) of 99m Tc-folate. SPECT/CT images and whole-body and lateral head planar images were acquired approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…32 Detection of FRα-expressing NFPA with 99mTc-Folate SPECT-CT helps in identifying tumours amenable to FRα-targeted therapy as demanded by the concept of personalized/precision cancer therapy which requires selection of patients for a specific targeted therapy based on molecular characterization of the tumour and its microenvironment. 98…”
Section: Medical Treatmentmentioning
confidence: 99%
“…32 Detection of FRα-expressing NFPA with 99mTc-Folate SPECT-CT helps in identifying tumours amenable to FRα-targeted therapy as demanded by the concept of personalized/precision cancer therapy which requires selection of patients for a specific targeted therapy based on molecular characterization of the tumour and its microenvironment. 98…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Previous studies have demonstrated that NF pituitary adenomas overexpress FRa compared with functioning pituitary adenomas. 8,12 Immunohistochemical analysis was performed on paraffin-embedded tissue sections using murine monoclonal antibodies to FRa, sections were examined by a single neuropathologist (M.M.L. ), and H-scores (0-300) were determined ( Fig.…”
Section: Fra Overexpressionmentioning
confidence: 99%
“…Folate receptor-α targeted liposomal doxorubicin had antiproliferative, antiinvasive and proapoptotic activity in primary cell cultures derived from patients with NFPA (98), thus potentially being of value for treating aggressive tumors. FR-α-expressing NFPA can be detected with 99m Tc-Folate SPECT-CT, thus identifying tumors amenable to folate receptor-targeted therapy (99).…”
Section: Octreotide-mediated Tumor-targeted Cytotoxic Drug Deliverymentioning
confidence: 99%